The effect of activity and face masks on exhaled particles in children - Peter P. Moschovis; Jesiel Lombay; Jennifer Rooney; Sara R. Schenkel; Dilpreet Singh; Shawheen J. Rezaei; Nora Salo; Amanda Gong; Lael M. Yonker; Jhill Shah; Douglas Hayden; Patricia L. Hibberd; et al. (Pediatric Investigation, 2023)
ABSTRACT Importance Despite the high burden of respiratory infections among children, the production of exhaled particles during common activities and the efficacy of face masks in children have not been sufficiently studied. Objective To determine the effect of type of activity and mask usage on exhaled particle production in children. Methods Healthy children were asked to perform activities that ranged in intensity (breathing quietly, speaking, singing, coughing, and sneezing) while wearing no mask, a cloth mask, or a surgical mask. The concentration and size of exhaled particles were assessed during each activity. Results Twenty‐three children were enrolled in the study. Average exhaled particle concentration increased by intensity of activity, with the lowest particle concentration during tidal breathing (1.285 particles/cm3 [95% CI 0.943, 1.627]) and highest particle concentration during sneezing (5.183 particles/cm3 [95% CI 1.911, 8.455]). High‐intensity activities were associated with an increase primarily in the respirable size (≤ 5 µm) particle fraction. Surgical and cloth masks were associated with lower average particle concentration compared to no mask (P = 0.026 for sneezing). Surgical masks outperformed cloth masks across all activities, especially within the respirable size fraction. In a multivariable linear regression model, we observed significant effect modification of activity by age and by mask type. Interpretation Similar to adults, children produce exhaled particles that vary in size and concentration across a range of activities. Production of respirable size fraction particles (≤ 5 µm), the dominant mode of transmission of many respiratory viruses, increases significantly with coughing and sneezing and is most effectively reduced by wearing surgical face masks.